METODE THINK PAIR SHARE UNTUK PENINGKATAN AKTIVITAS DAN PRESTASI BELAJAR SISWA TENTANG TATA NAMA SENYAWA KIMIA DI KELAS X MIA 4 SMA NEGERI 1 BABAT SEMESTER GENAP TAHUN PELAJARAN 2018/2019 - Chanifah Chanifah (Program Studi S1 Pendidikan IPA, FMIPA Universitas Pendidikan Ganesha, 2020)
To overcome the low activity and learning achievement, an active learning model is needed. The research objective was to describe the increase in creativity and student achievement using the think pair share method. The subjects of the research were 36 students of class X MIA 4, SMA Negeri 1 Babat. This research was conducted in two cycles, each cycle consisting of (1) planning (2) implementation (3) observation (4) reflection. The results of the study were 86.11% which was declared complete and an increase of 27.78%. For high student activity, an increase of 17.22% from the first cycle to the second cycle.